If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5) * squared = -9 Reorder the terms: (-5 + x) * squared = -9 Reorder the terms for easier multiplication: adeqrsu(-5 + x) = -9 (-5 * adeqrsu + x * adeqrsu) = -9 (-5adeqrsu + adeqrsux) = -9 Solving -5adeqrsu + adeqrsux = -9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: 9 + -5adeqrsu + adeqrsux = -9 + 9 Combine like terms: -9 + 9 = 0 9 + -5adeqrsu + adeqrsux = 0 The solution to this equation could not be determined.
| x+4i=-5+yi | | 5x+21=67 | | 12bx^2-7ax=0 | | 3x^2-10x=-1 | | 2/3y-7/4y=-13 | | -2x^2+12x=-36 | | 5y-1=3(y+3) | | 1-5x=4x+16 | | 3xsquared-10x=-1 | | 33c=726 | | 2(-4p-1)+(2.5-p)=x | | 5/2t-10=-30 | | 10x+30-20=90 | | 3.2b=1.8+3.6b | | f(x)=2x^3-8x^2+4x-16 | | 5y-2=28y | | 2b+42=7a+33 | | .25(r+8)=r-8 | | 4x+7x-4=56 | | 3x+12=-112 | | 4x+2=3x-16 | | s=2ab | | 4x+10+2x-20=90 | | 7(x-3)=3x+4x | | b^2-16b+70=0 | | 7b^2-b-6=0 | | x^2+y^2+19x-4y=0 | | 53+4b=11+2b | | b-28.2=5.7 | | 2t-11t= | | (5x-6)(x+1)= | | m/4-m |